Pemanfaatan Teknologi AI untuk Menyediakan Bahan Bacaan dalam Upaya Meningkatkan Literasi Digital Siswa di SMP Bina Muda Panggang - Sarjono, Sarjono; Rejokirono, Rejokirono (Universitas Sarjanawiyata Tamansiswa, 2025)
Students' digital literacy is a crucial 21st-century skill that goes beyond basic reading abilities, encompassing analytical, critical, and reflective comprehension. This study aims to explore the utilization of artificial intelligence (AI) technology in providing reading materials to enhance the digital literacy of students at SMP Bina Muda Panggang. The research employs a qualitative method with a descriptive design, involving 44 students and 10 teachers from July 22, 2024, to August 9, 2024. The findings reveal that AI-generated reading materials are more relevant and effective compared to conventional methods, with 85% of students completing the reading within 15 minutes, and 95% of students expressing that AI-based reading materials are more engaging. The study concludes that the use of AI can effectively enhance students' digital literacy and recommends the development of AI-based literacy programs and teacher training.